Nanotechnology for Targeted Detection and Removal of Bacteria: Opportunities and Challenges. Issue 21 (23rd September 2021) - Hajipour, Mohammad J.; Saei, Amir Ata; Walker, Edward D.; Conley, Brian; Omidi, Yadollah; Lee, Ki‐Bum; Mahmoudi, Morteza
Abstract: The emergence of nanotechnology has created unprecedented hopes for addressing several unmet industrial and clinical issues, including the growing threat so‐termed "antibiotic resistance" in medicine. Over the last decade, nanotechnologies have demonstrated promising applications in the identification, discrimination, and removal of a wide range of pathogens. Here, recent insights into the field of bacterial nanotechnology are examined that can substantially improve the fundamental understanding of nanoparticle and bacteria interactions. A wide range of developed nanotechnology‐based approaches for bacterial detection and removal together with biofilm eradication are summarized. The challenging effects of nanotechnologies on beneficial bacteria in the human body and environment and the mechanisms of bacterial resistance to nanotherapeutics are also reviewed. Abstract : Nanotechnologies are being used in the identification, discrimination, and removal of a wide range of pathogens. Pathogens, on the other hand, evolve over time and use different lines of defense and strategies to protect themselves against new treatments including nanotechnologies.